Effects of combination of linguistic and musical pitch experience on subcortical pitch encoding. (August 2018) - Maggu, Akshay Raj; Wong, Patrick C.M.; Antoniou, Mark; Bones, Oliver; Liu, Hanjun; Wong, Francis C.K.
Abstract: Musical experience and linguistic experience have been shown to facilitate language and music perception. However, the precise nature of music and language interaction is still a subject of ongoing research. In this study, using subcortical electrophysiological measures (frequency following response), we seek to understand the effect of interaction of linguistic pitch experience and musical pitch experience on subcortical lexical and musical pitch encoding. We compared musicians and non-musicians who were native speakers of a tone language on subcortical encoding of linguistic and musical pitch. We found that musicians and non-musicians did not differ on the brainstem encoding of lexical tones. However, musicians showed a more robust brainstem encoding of musical pitch as compared to non-musicians. These findings suggest that a combined musical and linguistic pitch experience affects auditory brainstem encoding of linguistic and musical pitch differentially. From our results, we could also speculate that native tone language speakers might use two different mechanisms, at least for the subcortical encoding of linguistic and musical pitch. Highlights: Combined effect of musical and linguistic pitch experience on brainstem encoding tested. Combined musical and linguistic experience does not enhance brainstem encoding of linguistic pitch. Combined musical and linguistic experience facilitates brainstem encoding of musical pitch. Different mechanisms of brainstem encoding for musical and linguistic pitch speculated.